Pemberdayaan Perempuan Melalui “Program Kas-Rpa” Di Lingkungan RW 05 Kelurahan Kendangsari - Siwi, Purwasih Diansiwi; Tukiman (CV. Ulil Albab Corp, 2025)
Most women are still marginalized compared to men in various sectors of life such as politics, economics, education, health and so on. Facing this problem, of course, the Surabaya City Government is trying to improve women's welfare, namely with the KAS-RPA (Women and Child Friendly Kampunge Arek Suroboyo) program. The aim of this research is to find out women's empowerment programs through the KAS-RPA program in RW 05, Kendangsari Village. The research method used is qualitative research with a descriptive approach. The data sources used are primary and secondary data. Data collection techniques through observation and literature study from official documents and articles according to the topic discussed. The results of the research show that women's empowerment in the RW 05 Kendangsari Village environment has increased quite well, supported by activities from the KAS-RPA program, although its implementation is not yet fully optimal.